Study of the mechanism of explosive force production on quick lift motion by analysis of EMG and motion - Nagao, H.; Yamada, H.; Ogawara, K.; Aruga, S.; Koyama, T.; Ozawa, Y.; Koganezawa, K. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this study is to investigate how explosive force exerts during power clean (PC) motion. The subjects are ten skilleds and ten unskilleds. The joint trajectory and EMG during PC are recorded. The joint torque and its rate of torque development (RTD) are calculated from the obtained data. The joint stiffness is estimated from joint stiffness index (JSI) calculated from EMG of agonist and antagonist muscle pair. Experimental results indicated that the skilleds showed the double knee bent that is typically seen in a stretch-shortening cycle (SSC). Skilleds exerted large values of RTD and JSI just after a period of exerting their small values during SSC. It indicates that a much amount of elastic energy stored in a low stiffness state is instantly transferred to the upper segments in the successive high stiffness state by "tenodesis action" of muscles. This is why large RTD generates in the skilled.